2018
DOI: 10.7150/thno.23877
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1-mediated microRNA expression signature predicts breast cancer outcome

Abstract: Background: Genetic classification of breast cancer based on the coding mRNA suggests the evolution of distinct subtypes. Whether the non-coding genome is altered concordantly with the coding genome and the mechanism by which the cell cycle directly controls the non-coding genome is poorly understood.Methods: Herein, the miRNA signature maintained by endogenous cyclin D1 in human breast cancer cells was defined. In order to determine the clinical significance of the cyclin D1-mediated miRNA signature, we defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
1
18
0
1
Order By: Relevance
“…Thus, a novel cyclin D1/miR-17-5p/miR-20 forms a regulatory feedback loop in breast cancer. Recently, differentially expressed miRNAs in a breast cancer cell line were determined using high-throughput screening [ 35 ]. These findings suggest that cyclin D1 acts as a regulator of miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a novel cyclin D1/miR-17-5p/miR-20 forms a regulatory feedback loop in breast cancer. Recently, differentially expressed miRNAs in a breast cancer cell line were determined using high-throughput screening [ 35 ]. These findings suggest that cyclin D1 acts as a regulator of miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…A cyclin D1-regulated miRNA signature, was identified in breast cancer cells that included several onco-mirs including miR-193b. When assessed in a superset of 459 breast cancer samples, the cyclin D1-regulated miRNA signature was associated with the Gormley 2 (G2) breast cancer miRNA subset, ERα + status and activation of the Wnt pathway [6]. Seed elements for cyclin D1-regulated miRNA were identified in 63 genes of the Wnt signaling pathway including DKK [6].…”
Section: Cyclin D1 Regulation Of the Non-coding Genomementioning
confidence: 99%
“…When assessed in a superset of 459 breast cancer samples, the cyclin D1-regulated miRNA signature was associated with the Gormley 2 (G2) breast cancer miRNA subset, ERα + status and activation of the Wnt pathway [6]. Seed elements for cyclin D1-regulated miRNA were identified in 63 genes of the Wnt signaling pathway including DKK [6]. These findings were consistent with studies conducted profiling a large number of different types of cancer cells that identified a distinct class of miRNAs (miR-193b, miR-193a-3p, miR-195-5p, miR-214-5p, miR-890) that target nearly all cyclins/CDKs.…”
Section: Cyclin D1 Regulation Of the Non-coding Genomementioning
confidence: 99%
See 2 more Smart Citations